2011
DOI: 10.1136/bjsm.2011.084038.37
|View full text |Cite
|
Sign up to set email alerts
|

The relationship between physical game demands and injury rehabilitation in international rugby union: a global positioning system analysis

Abstract: Background Over the past 10 years the methodologies and technology of recording professional rugby union game data has greatly improved with global positioning system (GPS) now the gold standard. Objective The aims of the present study were to evaluate the physical demands of the game at an international rugby union level using a GPS and establish the potential of the system in providing feedback to the management (sports medicine and coaching) team in relation to the mechanism/prevention of injury, as well as… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
5
0

Year Published

2012
2012
2013
2013

Publication Types

Select...
2

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(5 citation statements)
references
References 0 publications
0
5
0
Order By: Relevance
“…11 Despite the increased popularity in the use of GPS in Rugby Union in a clinical setting, only 2 studies have previously reported on the use of this technology to measure the physical demands of Rugby Union in 2 player positions. 3,4 The principal finding of the current study is that differences in these demands were observed using GPS technology in 8 player positions in an elite-club Rugby Union game. During the course of a game, players are required to use a range of energy systems combining low-intensity activity with intermittent bouts of various anaerobic high-intensity movements and power-based tasks in offense and defense phases of play.…”
Section: Discussionmentioning
confidence: 77%
See 3 more Smart Citations
“…11 Despite the increased popularity in the use of GPS in Rugby Union in a clinical setting, only 2 studies have previously reported on the use of this technology to measure the physical demands of Rugby Union in 2 player positions. 3,4 The principal finding of the current study is that differences in these demands were observed using GPS technology in 8 player positions in an elite-club Rugby Union game. During the course of a game, players are required to use a range of energy systems combining low-intensity activity with intermittent bouts of various anaerobic high-intensity movements and power-based tasks in offense and defense phases of play.…”
Section: Discussionmentioning
confidence: 77%
“…The function of GPS devices in sport and in Rugby Union has previously been described. 3,4,10 The GPS device in this study was protected using a plastic case and secured between the shoulder blades and upper thoracic spine using a custom-built harness. Higher sampling rates have been advocated in improving the reliability and validity of GPS devices, 10 and therefore data were sampled at a rate of 5 Hz.…”
Section: Methodsmentioning
confidence: 99%
See 2 more Smart Citations
“…In the context of this work, we refer to real time as the delivery of player measurements to coaches and staff with negligible delay between the actual event and the measurement delivery time. Recent studies have measured the physiological demands of professional rugby union using GPS sensing technology at both international test match [7] and club level [8]. GPS receivers, which are in constant signal contact with orbital satellites, track player position over time, and have primarily been used to measure player speed and distance travelled during training sessions of competition.…”
Section: Introductionmentioning
confidence: 99%